The role of the microbiome and psychosocial stress in the expression and activity of drug metabolizing enzymes in mice - Zemanová, Nina; Anzenbacher, Pavel; Zapletalová, Iveta; Jourová, Lenka; Hermanová, Petra; Hudcovic, Tomáš; Kozáková, Hana; Vodička, Martin; Pácha, Jiří; Anzenbacherová, Eva (Scientific reports, 2020)
The gut microbiota is involved in a number of different metabolic processes of the host organism, including the metabolism of xenobiotics. In our study, we focused on liver cytochromes P450 (CYPs), which can metabolize a wide range of exo- and endogenous molecules. We studied changes in mRNA expression and CYP enzyme activities, as well as the mRNA expression of transcription factors that have an important role in CYP expression, all in stressed germ-free (GF) and stressed specific-pathogen-free (SPF) mice. Besides the presence of the gut microbiota, we looked at the difference between acute and chronic stress. Our results show that stress has an impact on CYP mRNA expression, but it is mainly chronic stress that has a significant effect on enzyme activities along with the gut microbiome. In acutely stressed mice, we observed significant changes at the mRNA level, however, the corresponding enzyme activities were not influenced. Our study suggests an important role of the gut microbiota along with chronic psychosocial stress in the expression and activity of CYPs, which can potentially lead to less effective drug metabolism and, as a result, a harmful impact on the organism.
Keywords: Gene Expression Regulation, Enzymologic; střevní mikroflóra; Transcription Factors; systém (enzymů) cytochromů P-450; Mice, Inbred BALB C; transkripční faktory; Mice; myši inbrední BALB C; zvířata; Gastrointestinal Microbiome; messenger RNA; xenobiotika; regulace genové exprese enzymů; Stress, Psychological; mužské pohlaví; psychický stres; myši; Liver; Xenobiotics; Animals; RNA, Messenger; játra; Cytochrome P-450 Enzyme System; Male